Undergraduate Plastic Surgery Education: A National Survey of Clerkship Directors. Issue 2 (May 2018) - Morzycki, Alexander; LeBlanc, Martin; Williams, Jason
Background: The delivery of medical education has received increased attention in recent years due to ongoing time and financial constraints faced by medical educators. Given the recent calls to action by the Carnegie Foundation and Health Canada, an evaluation of the specialty education sector is warranted. To our knowledge, this is the first assessment of the Canadian plastic surgery undergraduate clerkship curriculum. Method: An anonymous electronic survey was distributed to the plastic surgery clerkship directors of all Canadian medical schools (N = 17). The survey consisted of Likert scales and open-ended short answer questions. Themes included general clerkship information, exposure characteristics, teaching characteristics, resource characteristics, and challenges and barriers faced by clerkship directors. Results: Survey response rate was 88%. All responding schools offered a clerkship rotation of varying length in time (1-4 weeks). Students had the most exposure to breast surgery (100%) and general plastic surgery (100%) and the least exposure to aesthetic surgery (40%). Sixty percent of schools indicated the use of modern educational methods. Resources available for teaching students varied. Rotations received excellent feedback from medical students (67%). More than half of respondents would like to see a universal, nationally formulated plastic surgery clerkship curriculum. Conclusion: There is significant heterogeneity in the delivery of plastic surgery clerkship in Canada. A number of areas for improvement have been identified. We hope to establish a national plastic surgery clerkship task force to address the concerns raised here and improve the delivery of undergraduate medical education. Assessment of students based on a national curriculum may help in decision-making regarding plastic surgery program admissions by introducing an element of standardization to clerkship exposure.